Inflation Targeting Pillars : Transparency and Accountability - Laxton, Douglas (IMF Working Papers; Working Paper ;, 2009)
This is the fourth chapter of a forthcoming monograph entitled "On Implementing Full-Fledged Inflation- Targeting Regimes: Saying What You Do and Doing What You Say." It examines a number of issues related to transparency and accountability in an inflation-targeting regime. It first looks at the factors behind the move to increased transparency in recent years and the important role of a communications strategy in transparency. It then turns to the role of the forecast in communications, how risks surrounding the forecast are communicated, and whether there should be limits on what is made public. It concludes with a short discussion of accountability.